Cannabidiol in patients with Lennox‐Gastaut syndrome: Interim analysis of an open‐label extension study. (11th February 2019) - Thiele, Elizabeth; Marsh, Eric; Mazurkiewicz‐Beldzinska, Maria; Halford, Jonathan J.; Gunning, Boudewijn; Devinsky, Orrin; Checketts, Daniel; Roberts, Claire
Summary: Objective: Patients with Lennox‐Gastaut syndrome (LGS) who completed 1 of 2 randomized, double‐blind, placebo‐controlled trials of add‐on cannabidiol (CBD) (GWPCARE3, NCT02224560 or GWPCARE4, NCT02224690) were invited to enroll in an open‐label extension (OLE) study evaluating the long‐term safety and efficacy of CBD (GWPCARE5, NCT02224573). Herein we present an interim analysis of the safety, efficacy, and patient‐reported outcomes from this trial. Methods: Patients received a pharmaceutical formulation of highly purified CBD oral solution (Epidiolex; 100 mg/mL), titrated from 2.5 to 20 mg/kg/d over a 2‐week titration period, in addition to their existing medications. Doses could be reduced if not tolerated or increased up to 30 mg/kg/d if thought to be of benefit. Results: This interim analysis was based on a November 2016 data cut. Of 368 patients who completed treatment in GWPCARE3 and GWPCARE4, 366 (99.5%) enrolled in the OLE study (GWPCARE5). Median treatment duration was 38 weeks at a mean modal dose of 23 mg/kg/d. Most patients (92.1%) experienced adverse events (AEs), primarily of mild (32.5%) or moderate (43.4%) severity. The most common AEs were diarrhea (26.8%), somnolence (23.5%), and convulsion (21.3%). Thirty‐five patients (9.6%) discontinued treatment due to AEs. Liver transaminase elevations were reported in 37 patients (10.1%), of whom 29 were receiving concomitant valproic acid; 34 cases resolved spontaneously or with dose modification of CBD or concomitant medication. Median reduction from baseline in drop seizure frequency (quantified monthly over 12‐week periods) ranged from 48% to 60% through week 48. Median reduction in monthly total seizure frequency ranged from 48% to 57% across all 12‐week periods through week 48. Eighty‐eight percent of patients/caregivers reported an improvement in the patient's overall condition per the Subject/Caregiver Global Impression of Change scale. Significance: In this study, long‐term add‐on CBD treatment had an acceptable safety profile in patients with LGS and led to sustained reductions in seizures.